Skip to main content

Subsection 5.2.6 Creating Predicate Logic Proofs II

This section contains some additional examples, including some with videos.

Subsection 5.2.6.1 Existential Instantiations, Then Universal Ones

Recall that, whenever we use Existential Instantiation, we must instantiate to some previously undefined element. Yes, we know that some element exists. But we know nothing else about it. But this isn’t so for Universal Instantiation. When we have a universal statement, its claim applies to all elements, and so, in particular, to any specific element we may be working with. Because of this difference, it generally makes sense, when we have a choice, to do Existential Instantiations first.

White Mammals

Suppose that we want to prove that there exists a white mammal. We have two premises:

x (Bear(x)  Mammal(x)) All bears are mammals.

x (Bear(x)  White(x)) There exists a white bear.

We can prove our claim as follows:

[1] x (Bear(x)  Mammal(x)) Premise

[2] x (Bear(x)  White(x)) Premise

[3] Bear(c*)  White(c*) Existential Instantiation [2]

[4] Bear(c*) Simplification [3]

[5] White(c*) Simplification [3]

[6] Bear(c*)  Mammal(c*) Universal Instantiation [1]

[7] Mammal(c*) Modus Ponens [4], [6]

[8] Mammal(c*)  White(c*) Conjunction [5], [7]

[9] x (Mammal(x)  White(x)) Existential Generalization [8]

We used Existential Instantiation in step [3], chose the name c*, and then used Universal instantiation to state the general claim in [1] as a specific claim about c*. If we’d tried to do those two instantiations in the opposite order, we’d have gotten stuck:

[1] x (Bear(x)  Mammal(x)) Premise

[2] x (Bear(x)  White(x)) Premise

[3] Bear(d)  Mammal(d) Universal Instantiation [1]

[4] Bear(c*)  White(c*) Existential Instantiation [2]

Oops. We can’t combine what we know about d with what we know about c*.

Subsection 5.2.6.2 Existential Instantiation and Generalization Proof Problem: Drug Test

DrugTest

Assume that if there is any woman who uses any medication then that woman may participate in our drug test. There is a woman who uses some medication. Thus, someone may participate in our drug test.

Assign the following names to basic statements:

W(x): True if x is a Woman.

U(x, y) True if person x Uses medication y.

P(x) True if x may Participate in our drug test.

Prove: ∀x (∀y ((W(x) ∧ U(x, y)) → P(x))) If there is any woman who uses any

medication then that woman may

participate in our drug test.

p (∃q (W(p) ∧ U(p, q))) There is a woman who uses some

medication.

∴ ∃z (P(z)) Someone may participate in our drug test.

You should do this proof yourself.

You can also watch our video, which will outline a strategy for creating a proof.

Video cover image

Subsection 5.2.6.3 Contradictory Premises Proof Problem: Funny

Assume that anyone who is funny is not sad. There is someone who is sad while everyone is funny. Thus, someone is richer than everyone.

Assign the following names to basic statements:

F(x): True if x is Funny.

S(x) True if x is Sad.

R(x, y) True if x is Richer than y.

Prove: ∀x (F(x) → ¬S(x)) Anyone who is funny is not sad.

x (∀y (F(y) ∧ S(x))) There is someone who is sad while everyone is funny.

∴ ∃x (∀y (R(x, y))) Someone is richer than everyone.

Yes, you are reading this correctly. The premises are about being funny and being sad, and the conclusion is about what appears to be something completely unrelated: wealth. Recall what we learned in Boolean logic about proving something that appears to come out of the blue.

You should do this proof yourself.

You can also watch our video, which will outline a strategy for creating a proof.

Video cover image

Subsection 5.2.6.4 Quantifier Exchange Proof Problem: Asleep in Class

Assume that Alice is in class. If Tom is asleep then it is not true that Alice is in class and Bob did his homework. If anyone is in class then everyone did the homework. Thus, it isn’t true that everyone is asleep.

Assign the following names to basic objects and statements:

A, B, T: Alice, Bob, Tom, respectively.

C(x): True if x is in Class.

H(x) True if x did his or her Homework.

S(x) True if x is aSleep.

Prove: C(A) Alice is in class.

S(T) → ¬(C(A) ∧ H(B)) If Tom is asleep then it is not true that Alice is in

class and Bob did his homework.

(∃y (C(y))) → (∀x (H(x))) If anyone is in class then everyone did the homework.

∴ ¬∀z (S(z)) It isn’t true that everyone is asleep.

You should do this proof yourself. You will notice that, since T stands for true in that system, the problem uses M in place of T.

You can also watch our video, which will outline a strategy for creating a proof.

Video cover image

Exercises Exercises

Exercise Group.
1.

Prove that this claim holds with no premises required:

(∃x (∀y (R(x, y)))) → (∀u (∃v (R(v, u))))

Hint: Recall the Conditionalization inference rule that we defined in Boolean Logic:

A, a set of premises

(Ap) entails q

pq

To use the rule, we assume whatever we want. Call it p. We prove that, with that assumption, along with whatever other premises we have (call them A), q must follow. We can then assert:

pq

This rule is useful in proving claims (as in this problem) of the form: pq.

(Here, we’ll just let A be the empty set of premises.) Remember that, to use this rule correctly, we begin by assuming p. We must then later (often at the end), “discharge” p by making it the antecedent of an implication.

Answer.

questionId: PsQs03

problemType: gradeLogicProof

questionTitle: Using Conditionalization

InitialProblemState: empty

questionDisplayText: Proving an implication without needing premises.

Solution.

[1] x (y (R(x, y))) (Conditional) Premise

[2] y (R(a*, y)) Existential Instantiation [1]

[3] R(a*, B) Universal Instantiation [2]

[4] v (R(v, B)) Existential Generalization [3]

[5] u (v (R(v, u))) Universal Generalization [4]

[6] (x (y (R(x, y))))  (u (v (R(v, u)))) Conditional Discharge [1], [5]

2.

Assume the following premises:

[1] ∃y (P(y)) → ∀x (Q(x))

[2] P(a)

[3] R(c) → ¬(P(a) ∧ Q(b))

Prove: ¬∀z (R(z)).

Answer.

Invoke Querium here.

questionId: PsQs04

problemType: gradeLogicProof

questionTitle: Practice with Quantifiers

questionDisplayText: none

hints: You may want to use Modus Tollens with premise 3. It’s a way to generate a claim about R.

[1] y (P(y)) → x (Q(x)) Premise

[2] P(A) Premise

[3] y (P(y)) Existential Generalization [2]

[4] x (Q(x)) Modus Ponens [1], [3]

[5] Q(B) Universal Instantiation [4]

[6] P(A)  Q(B) Conjunction [2], [5]

[7] R(C) → (P(A)  Q(B)) Premise

[8] R(C) Modus Tollens [6], [7]

[9] z (R(z)) Existential Generalization [8]

[10] z (R(z)) Quantifier Exchange [9]

3.

Assume the following premises:

[1] ∀x (∀y ((G(x) ∨ N(x, y)) → L(y)))

[2] ∃u (∃v (G(u) ∧ N(u, v)))

Prove: ∃z (L(z))

Answer.

Invoke Querium here.

questionId: PsQs05

problemType: gradeLogicProof

questionTitle: Practice with Quantifiers

questionDisplayText: Instantiating every quantified expression there is.

hints: Instantiate the existentially quantified expressions first. Then use the universally quantified ones to derive conclusions about the individuals that you know must exist.
Solution.

[1] x (y ((G(x)  N(x, y)) → L(y))) Premise

[2] u (v (G(u)  N(u, v))) Premise

[3] v (G(a*)  N(a*, v)) Existential Instantiation [2]

[4] G(a*)  N(a*, b*) Existential Instantiation [3]

[5] G(a*) Simplification [4]

[6] y ((G(a*)  N(a*, y)) → L(y)) Universal Instantiation [1]

[7] G(a*)  N(a*, b*)) → L(b*) Universal Instantiation [6]

[8] G(a*)  N(a*, b*) Addition [5]

[9] L(b*) Modus Ponens [7], [8]

[10] z (L(z)) Existential Generalization [9]

4.

Assume the following premises:

[1] y (x ((L(x) → N(x)) → G(y))) Premise

[2] x (G(x)) Premise

Answer.

Invoke Querium here.

questionId: PsQs06

problemType: gradeLogicProof

questionTitle: Practice with Quantifiers

questionDisplayText: Instantiating every quantified expression there is.

Solution.

[1] y (x ((L(x) → N(x)) → G(y))) Premise

[2] x (G(x)) Premise

[3] G(b*) Existential Instantiation [2]

[4] x ((L(x) → N(x)) → G(b*)) Universal Instantiation [1]

[5] (L(a*) → N(a*)) → G(b*) Existential Instantiation [4]

[6] (L(a*) → N(a*)) Modus Tollens [3], [5]

[7] (L(a*)  N(a*)) Conditional Disjunction [6]

[8] L(a*)  N(a*) De Morgan [7]

[9] L(a*) Simplification [8]

[10] L(a*) Double Negation [9]

[11] z (L(z)) Existential Generalization [10]